Diferencias en el desempeño exportador de las Pymes colombianas (2012)
This paper examines, for the period 2006-2011, whether or not there exist differences between activities, such as innovation, international business management, and barriers to export, carried out by a sample of small and medium size firms, wich are classiefied as permanent or esporadic exporters. We also explore whether or not such activities are relevant in determining not only the export status but also the export performance of both kinds of firms. The main results show that i) innovation and international business management are statistically significatn in determinating the export status; ii) permanent exporters tackle in a better way the barriers to export and; iii) the statistic evidence seems to support the idea that, at least for this sample of firms, instruments provided by the government to promote exports do no play a singnificant role in export performance in any kind of firm.